The Impact of Finance Practices on the Performance of Agricultural Small and Medium Enterprises in Mukono - Jonathan Ekwang (Uganda Christian University, 2025)
This research proposal aims to investigate the impact of finance practices on the performance of agricultural Small and Medium Enterprises (SMEs). Finance practices play a vital role in the financial management and decision-making processes of agricultural SMEs, yet there is a gap in understanding the specific practices that contribute to improved performance. This study seeks to address this gap by examining the relationship between finance practices and the performance indicators of revenue, profitability, and cash flow within agricultural SMEs. The research will adopt a mixed-methods approach, utilizing both quantitative and qualitative data collection methods. The quantitative analysis will involve collecting financial data from a sample of agricultural SMEs and conducting statistical analyses to identify the finance practices that correlate with superior performance. Additionally, qualitative data will be gathered through interviews and surveys to explore the challenges faced by agricultural SMEs in implementing effective finance practices. The anticipated findings of this research proposal will contribute to the existing literature by identifying the specific finance practices that have the greatest impact on agricultural SMEs performance. Moreover, it will shed light on the challenges faced by SMEs in implementing these practices and provide recommendations for overcoming such obstacles. Ultimately, this study aims to provide practical insights and guidance to agricultural SME owners and managers, policy makers, and industry stakeholders, enabling them to enhance financial performance and promote the growth and sustainability of agricultural SMEs in the current dynamic business environment.
Undergraduate